Essential oils from Vitex trifolia as an effective repellent for Aedes aegypti - Ni Luh Arpiwi; I Ketut Muksin; Eniek Kriswiyanti (Society for Indonesian Biodiversity, 2020)
Abstract. Arpiwi NL, Muksin IK, Kriswiyanti E. 2020. Essential oils from Vitex trifolia as an effective repellent for Aedes aegypti. Biodiversitas 21: 4536-4544. Vitex trifolia is a shrub or small tree grown wild from family Verbenaceae commonly found in the sandy shore habitat of the tropicals and sub-tropical countries. This research aims to measure the essential oils yield of V. trifolia leaves, to investigate the secretory cells of the leaf, and to measure repellent activity of the essential oils against Aedes aegypti. Leaves and soil samples were taken from Panjer, Sanur, and Sidakarya Villages of Denpasar, Bali Indonesia. Oil was extracted from fresh leaf samples using steam distillation. The essential oils were analyzed for its constituents using Gas Chromatography-Mass Spectrometry. The leaf cross-sections were prepared using paraffin embedding method and stained with safranin. The essential oils of V. trifolia at different concentrations (0, 2, 3, 4, 5, 6% w/w) were formulated into lotions. The yield of essential oils was significantly different from the three locations. The main constituent of the oil was cis-ocimene. The essential oil yield was positively correlated with the sand content. The secretory structures of the leaf were idioblast and glandular trichome. Lotions formulated with the essential oils were soft, not greasy, and not sticky upon application to the skin and non-irritant. Lotions with 5 and 6% essential oils gave 100% protection for 3 hours from Ae. aegypti.